O apoio pedagógico e a política de assistência estudantil: o contexto do Instituto Federal da Paraíba - campus Monteiro - Araújo, Tannissa Luanna Cardoso de (2024)
Pedagogical support, a provision under the National Student Assistance Plan (Pnaes) as established by Decree No. 7,234/2010, is crucial for higher education, particularly for students from disadvantaged backgrounds or those facing challenges that hinder their adaptation and integration into the academic environment. This support can ensure the necessary pedagogical assistance, fostering conditions that enable students to persist in their academic pursuits and achieve their objectives. This study investigates how pedagogical support, facilitated through the Student Assistance Policy, contributes to student retention in higher education programs. The primary objective is to analyze the actions undertaken by the pedagogical support team and their potential impact on student retention in higher technology courses at the Federal Institute of Paraíba (IFPB) – Monteiro Campus. This research employs a qualitative methodological approach, characterized by exploratory-descriptive, documentary, and bibliographic elements. The study population comprises students enrolled in the institution’s higher technology courses who have accessed the pedagogical coordination services. Data collection was conducted through questionnaires distributed via email to the students. Bardin’s (2016) content analysis method was utilized for data analysis. Based on the analysis, a practical guide for pedagogical interventions in higher education was developed as the final product. The findings indicate that pedagogical support is an essential tool for monitoring, guiding, advising, and assisting students throughout their academic journey. Factors influencing students’ academic decisions encompass personal, social, and institutional aspects. Thus, the existence of a comprehensive support network involving academic activities is vital to facilitate students’ progression within the institution.